Torque Ripple Reduction in Surface-Mounted Permanent Magnet Machine with Model-Based Current Reference Control - Gundogan, Abdulkerim; Bakan, Ahmet Faruk (MDPI, 2026)
Permanent magnet synchronous machines (PMSMs) are widely used in high-performance drive systems. However, parasitic torque ripple remains a critical limitation, causing acoustic noise, mechanical vibration, and speed fluctuations. This study presents a compact, model-based torque control strategy for surface-mounted PMSMs (SPMSMs) that suppresses torque ripple by generating a structured current reference. Grounded in the magnetic co-energy principle, the proposed method utilizes a deterministic analytical model to compensate for cogging torque and inductance harmonics, avoiding computationally intensive iterative estimators. A primary contribution involves adapting the harmonic injection profile to varying loads and magnetic saturation levels. Comprehensive finite element analysis (FEA) co-simulations demonstrate that the proposed method reduces torque ripple by approximately 87.5% and speed ripple by over 90% at 1500 RPM compared to conventional maximum torque per ampere (MTPA) strategies. Furthermore, extended dynamic analysis confirms superior robustness during start-up, transients, and low-speed operation (100 RPM), maintaining high control authority even under deep magnetic saturation (2.0 p.u.). Performance evaluations verify that this significant enhancement in torque quality is achieved with a negligible increase in total power losses (similar to 2.1%), presenting a computationally feasible solution for industrial embedded platforms.
Keywords: surface-mounted permanent magnet synchronous machines; torque ripple modeling and minimization; finite element analysis; machine parameter variation; advanced coupled simulation; DIRECT SPEED CONTROL; SYNCHRONOUS MACHINE; ROBUST ILC; PMSM; MINIMIZATION; DESIGN; COMPENSATION; DRIVES; MOTORS; Computer Science; Engineering; Physics